Menumbuhkan Minat Wirausaha yang Kreatif dan Mandiri Untuk Siswa Siswi SMA Negeri 1 Purwakarta - Dede Supendi; Wawan Oktriawan; Maya Nurhidayah; Dina Pebriani; Sherina Dwiyanti (Karunia: Jurnal Hasil Pengabdian Masyarakat Indonesia, 2024)
Entrepreneurship is not only limited to academic intelligence and skills in producing products but also a dynamic spirit in capturing challenges and risks and then turning them into opportunities and potential. Through this service activity, it is hoped that it can foster students' understanding and interest in the world of entrepreneurship so that the number of entrepreneurs grows and creates job opportunities so as to reduce the number of unemployed. In increasing interest in entrepreneurship, students are given an understanding of the importance of entrepreneurship. Entrepreneurship is full of risk and uncertainty, it can be successful and it can fail, for this reason it must be done with courage, tenacity and strong determination, to achieve a business that continues to develop, excels, is independent and can compete. The aim of this service activity is to foster interest in creative and independent entrepreneurship in students of SMA Negeri 1 Purwakarta in the following way: a) providing counseling in utilizing information technology in entrepreneurship, b) providing motivation and knowledge of entrepreneurship and entrepreneurship, c ) provide creativity and introduction to entrepreneurship independently from an early age.